Rhetorical and narrative style in "the progress of poetry" by Jonathan Swift - Santuso, Ahmad (Maliki Interdisciplinary Journal, 2024)
This study aims to explore and analyze the rhetorical and narrative style in the poem entitled "The Progress of Poetry" which was created by famous author Jonathan Swift. The data collection is done by searching, reading, and analyzing rhetorical style and narrative styles. This study will explore the various rhetorical techniques Swift uses, such as the use of hyperbole, parallelism, and irony, and how his narrative style provides strong meaning and supports the development of themes. A case study approach is also taken to explore the author’s and society’s response to the poets of the time with the existing situation and conditions. This research will provide a better understanding of Swift’s thoughts and how the literary work was used to critique and respond to literary and social changes in his environment.